Density dependence, landscape, and weather impacts on aquatic Aedes japonicus japonicus (Diptera: Culicidae) abundance along an urban altitudinal Gradient - Chaves, Luis Fernando (2017)
The Asian Bush Mosquito, Aedes (Finlaya) japonicus japonicus (Theobald) is an important globally invasive mosquito species. In comparison with other major invasive mosquitoes, relatively little is known about Ae. j. japonicus population dynamics in the field. Here, we present results from a 54-biweek long study of Ae. j. japonicus abundance in ovitraps set across the altitudinal gradient of Mt. Konpira, Nagasaki, Japan. Spatially, we found that Ae. j. japonicus fourth instar larvae (Aj4il) were more abundant at the base and top of Mt. Konpira and in ovitraps with more platykurtic water temperature (WT) distributions. In contrast, we found that temporally Aj4il were more abundant when ovitrap WT was more leptokurtic with 2 weeks of lag, and with high relative humidity SD with 2 months of lag. We also found that Aj4il were unlikely present when ovitrap WT was below 12.41°C. Parameter estimates for the Ricker model suggested that Ae. j. japonicus population growth was under density-dependence regulation, with a stable population dynamics whose fluctuations were associated with changes in ovitrap WT kurtosis and demographic stochasticity. Our results suggest that Aj4il abundance is more sensitive to temperature changes in kurtosis than mean values, potentially limiting the predictive ability of Ae. j. japonicus niche models based on the increase of average temperatures with global warming, and suggesting this mosquito species has a relatively coarse-grained response to temperature changes